2011
DOI: 10.14236/jhi.v19i3.807
|View full text |Cite
|
Sign up to set email alerts
|

Feedback and training tool to improve provision of preventive care by physicians using EMRs: a randomised control trial

Abstract: Background Electronic medical records (EMRs) have the potential to improve the provision of preventive care by allowing general practitioners (GPs) to track and recall eligible patients and record testing for feedback on their service provision. Objective This study evaluates the effect of an educational intervention and feedback tool designed to teach GPs how to use their EMRs to improve their provision of preventive care. Methods A randomised controlled trial comparing rates of mammography, Papanicolaou test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…EMR tools have been successful in assisting OB/GYN physicians in adherence to CCS guidelines transformation [ 29 ]. Since clinical data collection and use of data for population management in EMR systems are integral components of PCMH, it will be important to monitor its impact on improving the capacity of HCs primary care physicians to provide CCS and another preventive care [ 30 ]. Other common system-level solutions included changes in staffing such as either hiring new employees or increasing existing employees' hours as patient navigators, incorporating a quality improvement process, and implementing improved care management protocols [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…EMR tools have been successful in assisting OB/GYN physicians in adherence to CCS guidelines transformation [ 29 ]. Since clinical data collection and use of data for population management in EMR systems are integral components of PCMH, it will be important to monitor its impact on improving the capacity of HCs primary care physicians to provide CCS and another preventive care [ 30 ]. Other common system-level solutions included changes in staffing such as either hiring new employees or increasing existing employees' hours as patient navigators, incorporating a quality improvement process, and implementing improved care management protocols [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The limited evidence on the effectiveness of training in improving data quality in EHRs indicates that short-term, low-intensity training has limited impact (Maddocks et al 2011). As for other areas of behaviour change and skills development, substantial improvements in data quality are likely to require more intensive training associated with other strategies that are specifically designed to overcome the barriers to improvement as relevant to local contexts (Kaplan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Full-text screening was performed on the 19 retrieved studies. Twelve were identified that fit the previously specified inclusion criteria 23–34. The PreferredReporting Items for Systematic Reviews and Meta-Analyses flow chart was used to map out the study selection process as shown in figure 2.…”
Section: Resultsmentioning
confidence: 99%